Eficacia de la caléndula (caléndula officinalis), manzanilla (chamaemelum nobile) y la crema orenda® como cicatrizantes en heridas post operatorias en ooforohisterectomía lateral en caninos en una jornada de esterilización en popayán – cauca - Hernández Sotelo, Belkys; González Rodríguez, Jairo Andrés (Universidad Antonio Nariño, 2023)
The present degree work will be carried out in the city of Popayán-Cauca, with the main objective of demonstrating the level of effectiveness in the healing of postoperative wounds with the use of 3 plants with medicinal properties, comparing the treatment with them, the evolution and progress in operated patients. Ointments prepared with Aloe vera (Aloe vera), Calendula (Calendula of icinalis), and chamomile (Chamaemelum nobile) will be used in the post-surgical healing processes of sterilization by lateral ovariohysterectomy in canines. Taking as evaluation parameters the changes presented in the postoperative wound in the first 21 days of care in a total of 15 patients. The patients will be divided into 4 four working groups, each group will be made up of 5 animals; Group 1: consists of 5 patients who will be medicated with concentrated Calendula concentrated ointment (Calendula of icinalis); Group 2: will have 5 patients who will be medicated with concentrated chamomile ointment (Chamaemelum nobile). Finally, Group 3, or control: Will have 5 patients medicated with an allopathic commercial brand ointment. Lateral ovariohysterectomy, apart from having rapid healing and not presenting many signs in the wound, is also an aesthetic technique, since over time the animal does not present a surgical scar, for this reason, it is intended to show which of the components proposed to allow to improve the healing process, using plants as an alternative treatment for their components and benefits in terms of costs and natural healing characteristics.